PERKEMBANGAN HUKUM KEWARISAN ISLAM DI INDONESIA (Studi Perbandingan Hukum Kewarisan Dalam Kompilasi Hukum Islam Dengan Hukum Kewarisan Dalam Fiqih Konvensional ) - Ahmad Saifudin; Akhmad Khisni (Jurnal Akta, 2017)
The study entitled "The Development of Islamic Inheritance Law in Indonesia (Comparative Study of Inheritance Law in Compilation of Islamic Laws With Legal Inheritance In Conventional Fiqh)" This study uses a normative juridical approach, in collecting data more emphasis on primary source material, in the form of legislation, Reviewing the rules of law as well as the theory of jurisprudence in addition to interviews to the parties related to the issues in the perusal. Based on these methods the research produces in essence: The forms of legal development of inheritance in the KHI incorporate many elements of customary law and the interests that Indonesians need today. So many forms of inheritance law have not been contained in the fiqh of the conventional (fiqh al-mawarits), but it has been contained and codified in the law of KHI inheritance, among others: article 171 on Joint Treasure, article 177 on the division of father asabah. Article 209 stating that foster and adopted sons receive inheritance, and if they do not receive a will, then they are entitled to a will. And KHI also acknowledged the gono-gini institute whereas the classical fiqh does not admit it (not make sub discussion). In addition, there are contradictions of the inheritance law policies contained in the KHI between the one article and the other articles, among others: article 176 on the distribution of boys and girls. This is contrary to article 229 (which is the closing provision), which states that in settling cases, the judge shall observe the values of the living law in society so that his judgment is in accordance with the sense of justice. In this case, the Indonesian Court, often inheritance distribution is not based on the principle of 2 to 1 for boys and girls. Also, article 183 on peace in the distribution of inheritance which may be contradictory to article 176. Likewise, article 185 on the successor heirs and article 189 on the wholeness and unity of agricultural land of less than 2 (two) hectares, contrary to the principle of ijbari in Islamic inheritance law (fiqh conventional).Keywords: Law of Inheritance, KHI, Conventional Fiqh.